Application of integrated treatment strategies for explosive industry wastewater—A critical review. (June 2020) - Bhanot, Pallvi; Celin, S. Mary; Sreekrishnan, T.R.; Kalsi, Anchita; Sahai, S.K.; Sharma, Praveen
Highlights: Review focuses on integrated treatment processes for explosive industry wastewater. Comparative efficiency of individual and combined treatment technologies. Field scale applications of integrated processes for explosive industry wastewater. Future scientific prospects for integrated wastewater treatment. Abstract: Environmental pollution caused by explosive chemicals is a matter of concern. Explosives enter the environment during manufacturing, firing, loading, assembling, and packing operations. Explosive contaminated wastewater if released untreated, deteriorates the quality of vital environmental components viz. lithosphere, hydrosphere and biosphere. Therefore, treatment of these hazardous compounds present in the wastewater is essential before release into the environment. Many conventional treatment techniques have been employed for the explosive wastewater decontamination, which are based on physical, biological and chemical methods. These techniques do not ensure complete elimination of the contaminant; instead they merely transfer the contaminants from one phase to other. The ultimate goal of any treatment technology is to achieve complete mineralization of the contaminant, which would be possible by integrating appropriate technologies. Integrated treatment technologies using the combined efficiencies of physico- chemical and biological processes have proven successful in treating explosive wastewater. This review paper provides an insight on the scientific prospects of integrated treatment concepts. Factors influencing the treatment efficiency of combined treatment approaches and critical advantages and disadvantages of various integrated treatment schemesare included in the review. Application of environmental sustainability concepts such as life cycle assessment, simulation and modelling studies and adoption of circular economy approach are the future scientific prospects of explosive wastewater treatment which are detailed in the paper. Finally, recommendations for sustainable treatment of ammunition factory effluent are also highlighted. From review of available literature, it is clear that process integration has more advantages than single treatment process for managing explosive industry wastewater.